Carbon monoxide (WHO, 1999)
Evaluates the risks to human health and the environment posed by exposure to carbon monoxide a colourless odourless gas produced by both natural and anthropogenic processes. Concerns about the potential health effects of exposure have been addressed in extensive studies with both humans and a range of animal species. Although studies of carbon monoxide poisoning are included the report gives major attention to possible health risks linked to the relatively low concentrations that characterize most exposures. The report also aims to identify subpopulations that may be especially susceptible to adverse health effects. Close to 1000 references are included in this comprehensive assessment.Concerning environmental levels arising from human activities highway vehicle emissions are considered the principal source followed by emissions from non-highway transportation sources other fuel combustion sources industrial processes and solid waste disposal. Evidence from monitoring stations supports the conclusion that environmental concentrations are declining reflecting the efficacy of emission control devices on newer vehicles. The report also considers the factors that contribute to indoor concentrations with cigarette smoke singled out as a major source.A chapter on environmental distribution and transformation summarizes what is known about the environmental fate of carbon monoxide its contribution to ozone production in the troposphere and its possible role in global warming. Sources of personal exposure are considered in the next chapter which concludes that the most important exposures for the general population occur in the vehicle and indoor macroenvironments. Several occupations involving an increased risk of high exposures are also identified. Toxicokinetics and mechanisms of action are reviewed in the next chapter which discusses the many factors that influence the concentrations of carboxyhaemoglobin in blood and summarizes what is known about the primary mechanisms by which carboxyhaemoglobin formation exerts its toxic effects. The remaining chapters consider adverse effects on health. A review of the abundant findings from animal studies helps elucidate the mechanisms of carbon monoxide toxicity. Studies of developmental toxicity provide strong evidence that maternal exposure produces reductions in birth weight cardiomegaly delays in behavioural development and disruptions in cognitive function.A chapter on health effects in humans considers numerous investigations of adverse effects linked to typical ambient exposure levels. Findings are summarized in terms of damage to the cardiovascular and respiratory systems effects on neurobehavioural functions developmental toxicity and other systemic effects. Also considered are the effects of exposure at high altitudes in users of psychoactive drugs and in combination with exposure to other air pollutants. An evaluation of high-risk groups concludes that patients with reproducible exercise-induced ischaemia are a sensitive group at increased risk for experiencing adverse health effects. The report also found evidence indicating that exposure may cause an increased risk of sudden death from arrhythmia in patients with coronary artery disease. The report further concludes that exposure during pregnancy and early childhood carries a number of important risks.Concerning accidental exposure to high concentrations the report concludes that carbon monoxide poisoning occurs frequently has severe consequences including immediate death involves complications and late sequelae and is often overlooked.Among its many other conclusions the report calls for better education of the general population about the risks of exposure especially in individuals with cardiovascular and respiratory disease and better awareness among medical professions of the dangers of carbon monoxide exposure during pregnancy.
Environmental health criteria, ISSN 0250-863X No. 213
Keywords: rizikové faktory; environmentální vědy; environmentální zdraví; Risk Assessment; vystavení vlivu životního prostředí; Carbon Monoxide; Risk Factors; hodnocení rizik; Environmental Health; Environmental Exposure; toxikologie; oxid uhelnatý; Environmental Monitoring; monitorování životního prostředí